Conserved transport mechanisms but distinct auxin responses govern shoot patterning in Selaginella kraussiana. - Sanders, H; Langdale, J (2013)
To provide a comparative framework to understand the evolution of auxin regulation in vascular plants, the effect of perturbed auxin homeostasis was examined in the lycophyte Selaginella kraussiana. Polar auxin transport was measured by tracing tritiated IAA in excised shoots. Shoots were cultured in the presence of auxin efflux inhibitors and exogenous auxin, and developmental abnormalities were documented. Auxin transport in Selaginella shoots is exclusively basipetal, as in angiosperms. Perturbed auxin transport results in the loss of meristem maintenance and abnormal shoot architecture. Dichotomous root branching in Selaginella appears to be regulated by an antagonistic relationship between auxin and cytokinin. The results suggest that basipetal polar auxin transport occurred in the common ancestor of lycophytes and euphyllophytes. Although the mechanisms of auxin transport appear to be conserved across all vascular plants, distinct auxin responses govern shoot growth and development in lycophytes and euphyllophytes.